The Power to Administer Land in Ethiopia: Scrutinizing Federal Legislative Interventions - Semahagne, Habtamu Sitotaw (Bahir Dar University Journal of Law, 2022)
This article examines the legislative interventions of the Federal Government against States’ power to administer land in Ethiopia. The Ethiopian federal system prohibits interventions against the functions assigned to one level of government. Nonetheless, when the Federal Government enacted the Urban Lands Registration Proclamation No. 818/2014 and it took the power to allocate land parcels above 5000hrs to investors from States by delegation, the process results for legislative intervention as it is contrary to what the federal system requires. Being qualitative methodologically, the article assessed the FDRE Constitution and relevant federal and regional rural land laws; reviewed related literature and conducted interviews. Following detailed analysis on the issues, the article recommends that the transferred land allocation power for investors shall be returned to States. Also, enacting urban land registration law should have been left to States by virtue of residual power under the Constitution.